Fast Local Transient Solution Of Micro-Channel Heat Sink Using A Symptotic Waveform Evaluation - Lin, Beh Shiao (2010)
Thermal analysis of one-, two- and three-layered micro-channels have been carried out. Seven types of micro-channels have been identified based on all the possible types of flow directions. Finite element methods (FEM) is used to discretise the domain into nodes and elements, and then Galerkin\'s weighted residual method is used to reduce the equation from a second order partial differential equation to a first order ordinary differential equation. Asymptotic waveform evaluation (AWE) then takes over the formulation steps, by obtaining the transient response equation of one node per calculation. The verification of AWE result is done by comparing the transient response equation with FEM, and the steady state results have also been verified by comparing the thermal resistance from other literatures.